Developing Student Worksheets Based on Problem Posing Approach to Improve Students' Reasoning Ability - Farman Farman; Meyta Vivin (Pendidikan Matematika UNIMOR, 2024)
This research aims to obtain problem-posing-based student worksheets that are valid, practical, and effective. This type of development research aims to produce products through problem posing-based student worksheets. The development of problem posing-based worksheets is carried out through Four-D steps consisting of define, design, development, and disseminate. The test subjects in this research were 8th-grade students at Muadz Bin Jabal Kendari. The instruments used in data collection consisted of a validation sheet, a response questionnaire for using problem-posing-based student worksheets, and a reasoning ability test. The results of the research show that (1) the validation results with an average score of 4.6, which means that the problem posing-based student worksheets are within the criteria of being very valid and suitable for use, (2) The results of the analysis of student responses to the use of problem posing-based student worksheets show that the average response The student's class is 88.54, which means the class response is positive and is included in the practical category. (3) Students' reasoning abilities on the circle concept have an average score of 76.0, and based on the established criteria, the average level of students' reasoning is categorized as high. This shows that the problem posing-based student worksheets meet the effective category. Thus, problem posing-based student worksheets are valid, practical, and effective for learning circle material.